New patterns of learning during the Pandemic Crisis of 2019 - Madouni, Ali (Technium Social Sciences Journal, 2022)
Education institutions and learning operations are part of the hardest hits of the Corona pandemic crisis of 2019. In addition to the sudden breakdowns of vital-life sectors and education, the learning and teaching processes knew some disorders and interruptions differently worldwide. Not only that, but also this crisis brought its effects on students and school children; especially concerning their psychological health due to the restrictions of lockdown and social distancing, over and above that these generations have neither precedent with inevitable crisis, nor procedures. Education in the age of Corona is a primary concern and challenge for countries, especially in the light of the unequal levels of alternative solutions to pursue the teaching process regularly and with lesser damages. This article aims to raise awareness about the novel patterns and platforms that have been used globally since the pandemic's emergence. Furthermore, it addresses their effectiveness in large parts of countries. It attempts to assess their performance and compare the extent of responsiveness to these teaching platforms and technologies in different countries. At the end of this suggested contribution, we intend to track the future of these patterns and platforms in the post-corona phase.